Improvement of the acceptance of the city multidisciplinary hospital - S. A. Suslin; A. V. Vavilov; R. I. Ginnyatulina (Исследования и практика в медицине)
Purpose of the study. Improving the work of the admission department of a large multidisciplinary hospital with the help of new organizational technologies.Materials and methods. The basis of the study is N.I. Pirogov Samara State Clinical Hospital No. 1. The paper used methods of organizational modeling and statistical analysis.Results. Prior to the introduction of new organizational patient-oriented technologies, the following problems were identified in the hospital admission department: mixing flows of planned and emergency patients, patients with a neurological and cardiology profile, patients receiving paid services; the inability to provide resuscitation in the ward; ineffective routing and coordination of patients; the start time for medical care ranged from 30 minutes to 3 hours. After improving the organization of medical care in the admission department, the infrastructure, the order of the department, the staffing of the department and the logistics of patients changed. The flows of patients were divided, zones for emergency patients were allocated: the “red zone” is intended for patients in an extremely serious condition with impaired vital functions; The "yellow zone" is intended for patients who are in a serious condition or in a state of moderate severity, with impaired self-movement, the "green zone" is intended for patients whose health condition does not threaten life. As a result of the introduced changes, the time to begin providing medical care to patients in serious condition was reduced to 1–2 minutes, the time spent by patients in the admission department was reduced to an average of 40 minutes, the number of outpatients received over the past three years increased by 37.7% (from 15528 to 21387).Conclusion. As a result of improving the work of the admission department, the time spent by patients in the admission department was reduced; increased throughput of the department; qualitative and quantitative indicators of work have changed.